Isotope stratigraphy of Precambrian sedimentary rocks from Brazil: Keys to unlock Earth's hydrosphere, biosphere, tectonic, and climate evolution - Caxito, Fabricio de A.; Uhlein, Gabriel J.; Uhlein, Alexandre; Pedrosa-Soares, Antonio Carlos; Kuchenbecker, Matheus; Reis, Humberto; Sial, Alcides N.; Ferreira, Valderez P.; Souza Alvarenga, Carlos Jose; Santos, Roberto Ventura; Vieira, Lucieth Cruz; Dantas, Elton; et al. (Elsevier B.V., 2019)
Brazil is a natural laboratory for the application of isotope stratigraphy tools on the study of Precambrian sedimentary successions, with excellent registers of Archean, Paleo, Meso, and Neoproterozoic age. Those successions witnessed the most extreme and unidirectional events in Earth's history, such as the Paleoproterozoic and Neoproterozoic oxygenation events (GOE and NOE), the main stages of iron formation deposition, the global Cryogenian glaciations and the explosive diversification of metazoans near the Precambrian/Cambrian border. Chemical sedimentary rocks such as carbonates, iron formations and evaporites that can act as natural recorders of seawater composition are present in all of those successions and furnish important pieces of evidence in order to reconstruct the chemostratigraphic record. The field of isotope stratigraphy keeps expanding in Brazil and novel information from developing isotopic systems will surely add to the growing database and provide important information on Earth's ancient biogeochemical cycles in the years to come.